Controle PI adaptativo fuzzy aplicado a um motor síncrono de ímãs permanentes - Baumel, Rafael Schmidt (2018)
The Permanent Magnet Synchronous Motor (PMSM) presents wide application in industry, in general, in electrical vehicles and wind power generators. This machine has several advantages over others like AC or DC machines, as high power density, high efficiency and low maintenance cost. In this context, this project presents a study about control techniques applied to this electric motor. The main target is to control the speed of the PMSM through the control techniques, by means of simulations and experimental tests, and evaluate the best output response. Initially the characteristics and employability of the PMSM are studied. Then, a classical mathematics modeling in D and Q reference frame of the rotor are analyzed. The space vector modulation is also analyzed, due to common use on three-phase motor drives, and for facilitating the implementation in an embedded system. In sequence, the development of the inner loop current control and the external loop speed control for the PMSM are accomplished, and this case, two control techniques, a PI control and an adaptive PI using Fuzzy logic are used. A PI control is used due its simplicity and good output response and avoid problems inherent to the derivative component of the PID. An adaptive PI tuned by fuzzy logic is used, due to its ability to adapt the control action according to operating conditions such as disturbance or load variations. The work presents experimental verification through simulations and a physical prototype with control made by high performance microcontroller. Simulation results in Matlab/Simulink to validate the control system design are presented and compared with the experimental results.